Impact of neoadjuvant targeted therapy on perioperative complications in patients with localized reno-cellular cancer - O. A. Voylenko; O. E. Stakhovskyi; O. A. Kononenko; S. L. Semko; M. V. Pikul; Yu. V. Vitruk; E. O. Stakhovsky (Клінічна хірургія, 2020)
Objective. To study the efficacy of neoadjuvant targeted therapy in treatment of localized reno-cellular cancer and to determine its impact on the perioperative complications rate.